An active convective 4He heat switch - May, AJ; Azzoni, S; Melhuish, S; Piccirillo, L; Seal, D; Sweetnam, T; Winnicki, J (Elsevier, 2022)
The design and experimental demonstration are reported of an active convective heat switch suitable for use at cryogenic temperatures. The switch is mechanically simple, relatively inexpensive, and requires no moving parts, instead being operated entirely using heaters. The working gas used is <4> He in a closed cycle and, as such, the switch requires no external gas connections. Closed conductances on the order of 50 mW/K have been demonstrated with residual open conductances on the order of 0.4 mW/K. Novel modelling is presented which shows excellent agreement with the experimental data and significant improvement over existing models.